SIPD at The Intersection of Regional Policy and Capacity: Evaluation of The Implementation of Permendagri 70/2019 at The DPUPR of Banten Province - Hastuti, Dwi; Stiawati, Titi; Riswanda, Riswanda (Dinasti International Journal of Education Management and Social Science, 2025)
The digitalization of regional financial governance in Indonesia requires local governments to adopt integrated information systems to enhance transparency and accountability. Minister of Home Affairs Regulation No. 70 of 2019 mandates the Regional Government Information System (SIPD) as a unified platform for regional financial management. However, its implementation at technically complex agencies, such as the Banten Province Public Works and Spatial Planning Agency (DPUPR), still faces significant challenges. This study evaluates SIPD implementation using the CIPP (Context, Input, Process, Product) model through a qualitative descriptive-evaluative approach involving interviews, observations, and document analysis. The findings show that SIPD is contextually well-aligned with regulatory requirements and organizational needs. Nevertheless, limitations persist in human resource capacity, IT infrastructure, system stability, and user competency distribution. Despite these challenges, SIPD has improved data consistency, reporting efficiency, and audit trails. The study concludes that institutional readiness and organizational adaptability are more critical to SIPD success than technological factors alone, highlighting the need for capacity building, infrastructure improvement, and strengthened inter-unit coordination.